Experience as a source of knowledge in divestiture decisions: emerging issues and knowledge management implications. Issue 2 (12th February 2018) - Peruffo, Enzo; Marchegiani, Lucia; Vicentini, Francesca
Abstract : Purpose: This paper aims to analyse the idea that experience acts as an antecedent in divestiture and triggers an organisational learning process that enables the divesting firm to convert experience into knowledge, increasing the probability that a firm will undertake subsequent divestitures. Design/methodology/approach: The approach is quantitative. The research project used a case–control design, with a sample consisting of 274 divesting and non-divesting firms. Given the dichotomous nature of the dependent variable, the relations of the research model are tested using logistic regression. Findings: The likelihood of a divestiture increases when firms have already had past experience of divestitures. Firm performance and firm size act as moderating variables, that is, the learning effects are weaker in firms with better past performance and also in larger firms. Research limitations/implications: The study contributes to the literature on organisational learning and divestiture. In particular, the knowledge obtained from previous divestitures is positively related to subsequent ones. The results on firm size and performance as contingency factors make it possible to distinguish between the different learning mechanisms in proactive and reactive divestitures, as well as in larger and smaller firms. Accordingly, a two-level framework of experience and knowledge is proposed. Practical implications: The results are of interest for practitioners who need a better understanding of the antecedents of their strategic actions in terms of past experience and knowledge. The study also offers insights into the knowledge management practices that fit into the proposed two-level framework of knowledge accumulation. Originality/value: The originality of the study consists in the strong evidence of learning effects in divestitures that it finds. This study augments a promising line of research on the effect of experience in rare strategic decisions, enriching our understanding of the learning mechanisms associated with complex experiences.